Bilateral Asynchronous Renal Cell Carcinoma with Metastatic Involvement of the Tongue - Naseem Ghazali; Charlotte Davis; A. W. Barrett; John V. Tighe (Hindawi Limited, 2012)
Renal cell carcinoma (RCC) has a propensity for distant organ metastasis and late recurrence, involving not only the ipsilateral but also contralateral kidney. Lingual metastasis by RCC is rare. We present an unusual case of bilateral asynchronous RCC. Involvement of the right kidney was discovered only after a metastatic tongue lesion was diagnosed. The original RCC had been treated by left nephrectomy 14 years previously. Due to end-stage primary pulmonary malignancy, and poor function of the remaining kidney, immunotherapy was unsuitable. Palliative local resection of the lingual metastasis alleviated functional difficulties and was preventative against airway obstruction, but the patient died five months later.